Error vector magnitude measurement and analysis in optical communication system - Junsen LAI; Xiaohua TANG; Rui TANG; Xin ZHAO; Wenyu ZHAO; Haiyi ZHANG (Dianxin kexue)
Vector modulation format of high speed optical communication system calls for new measurement and analysis scheme.Error vector magnitude (EVM) is one of the most important parameters in vector modulation evaluation.The definition of EVM parameters,its test methods and instruments were analyzed,and application of EVM related parameter in transmitter measurement and its standardization progress were also discussed.